Identity Reorganization Among Primiparous Cameroonian Adolescents: From the Status of Daughter to the status of Mother - Ndje, Ndje Mireille (Journal of Behavior Therapy And Mental Health, 2024)
Adolescence in Cameroon, as in many parts of sub-Saharan Africa, is often marked by early childbearing. Studies have shown a national prevalence of adolescent deliveries to be around 14.2% - 14.4%, a higher rate than the average for sub-Saharan Africa This presents a unique challenge for young mothers, who must navigate the complex process of identity reorganization while still navigating their own adolescence with its multiple changes. This article explores the experiences of primiparous (first-time) Cameroonian adolescents as they transition from daughters to mothers. The objective of this article is to understand how identity reorganization takes place among primiparous Cameroonian adolescents who pass without transition from the status of daughter to the status of mother. Drawing on qualitative data from semi-structured interviews, with seven participants chosen on the basis of selection criteria, the article examines the psychological, social, and cultural factors that shape this identity shift. An interview guide with three main themes made it possible to collect verbatim comments from the participants. The thematic analysis highlights the challenges faced by these young mothers, such as navigating social stigma, managing emotional upheaval, and balancing motherhood with their own developmental needs. The findings of this study highlight the complex and multifaceted nature of identity reorganization among primiparous Cameroonian adolescents. The social stigma associated with early childbearing, coupled with the emotional and practical demands of motherhood, can pose significant challenges to these young women. However, a study on a larger sample could reveal the resilience and resourcefulness of some adolescents, who find support within their communities and employ various coping mechanisms to navigate this transition. Finally, the article discusses the implications of these findings for adolescent maternal health interventions and social policy in Cameroon.
Keywords: Identity; adolescence; motherhood; primiparous; daughter; mother